2006
DOI: 10.1063/1.2364183
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic oscillators coupled by springs: Discrete solutions as a Wigner quantum system

Abstract: We consider a quantum system consisting of a one-dimensional chain of M identical harmonic oscillators with natural frequency ω, coupled by means of springs. Such systems have been studied before, and appear in various models. In this paper, we approach the system as a Wigner Quantum System, not imposing the canonical commutation relations, but using instead weaker relations following from the compatibility of Hamilton's equations and the Heisenberg equations. In such a setting, the quantum system allows solut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(77 citation statements)
references
References 34 publications
1
76
0
Order By: Relevance
“…In [7], it was shown that one can relax the canonical commutation relations for the operatorŝ q r andp r , leading to a larger class of solutions for the system described by (2.1). This is known as a Wigner Quantum System approach [9,10].…”
Section: System With Periodic Boundary Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [7], it was shown that one can relax the canonical commutation relations for the operatorŝ q r andp r , leading to a larger class of solutions for the system described by (2.1). This is known as a Wigner Quantum System approach [9,10].…”
Section: System With Periodic Boundary Conditionsmentioning
confidence: 99%
“…The system studied in [7] consists of a string or chain of n identical harmonic oscillators, each having the same mass m and frequency ω. The position and momentum operator for the rth oscillator (r = 1, 2, .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations